Metode Takhrijul Furu’ Alal Ushul: Pilar Dinamis Dalam Istinbatul Hukum Islam - Muhammad Akbar Hilman; Muhammad Azrul Amirullah (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Sharia law is a legal product derived from the Qur'an and Sunnah through the ijtihad of scholars using established legal reasoning principles. The method of legal reasoning itself was not formally codified at the time. It existed during the lifetime of the Prophet Muhammad (peace be upon him) and his companions. After the Prophet returned to his Lord, the method of legal reasoning was adopted by the Companions who were well-versed in Islamic law. They analysed the textual sources of Islamic law and the explanations of the Prophet Muhammad, peace be upon him, before establishing the law. This practice was continued by the Tabi’in and Tabiut Tabi’in in subsequent generations in the process of legal reasoning, which later became known as the Mujtahid. These Mujtahid imams were the ones who established the principles of legal reasoning in the history of Islamic law. The type of method used in this research is the literature review method. This method was chosen because it facilitates the search for research discussions. The approach used includes a conceptual approach. Thus, the ability to derive legal rulings from sources of Islamic law will develop gradually, in line with increasing experience and understanding of the maqashid syariah—the primary objectives of Islamic law itself. A student will also develop sensitivity to societal dynamics and be able to distinguish between matters that are fixed (tsawabit) and those that are variable (mutaghayyirat). This is important so that the laws produced remain relevant, functional, and flexible in the face of modern times. Additionally, this training fosters the spirit of ijtihad and scientific courage in deriving new laws, especially amid the rapid pace of globalisation, technological advancements, and the emergence of social phenomena unprecedented in classical times. They will also become accustomed to reading classical and contemporary literature comparatively, thereby broadening their perspective on fiqh, making it tolerant and not narrow-minded.